Factors influencing the social perception of entrepreneurs in Spain: A quantitative analysis from secondary data - Arroyo Barrigüete, José Luis; Escudero Guirado, Carmen; Minguela-Rata, Beatriz (My University, 2023)
.

The essential role that entrepreneurs play in the economy, while acknowledged in the academic context, is not always recognized socially. In the specific case of Spain, the profession has even been called into question by public institutions, which is highly detrimental to both the social image of entrepreneurs and the country’s economy. Therefore, there is a need to identify factors that can improve this social image. This study aims to investigate one of these factors, specifically the effect of interest in economics. To do so, data from a large sample of 25,835 Spanish citizens from 2002–2022 were employed. The analysis was conducted using a combination of a neural network model and logistic regression. The conclusion of the study is that as interest in economics and business increases, the perception of entrepreneurs improves. Therefore, those individuals with less interest in economics tend to have a more negative view of this profession. This result opens up a potential avenue for enhancing the social image of entrepreneurs, as a higher interest in economics and business, which could be achieved through effective communication campaigns or basic education, leads to an improvement in perception.
Artículos en revistas
Keywords: Innovación docente y Analytics (GIIDA)